Desensitization vs. coping skills training in combination with tell-show-do method as behavior management techniques for 5-6 year old pediatric patients on their initial dental visit - Angeles, Agnes Grace
It is imperative to condition the behavior of the child beforehand in order for him to accept the dental treatment. Thia study is in search of a more effective behavior management technique which could be recommended to clinicians. The population consisted of 30 kindergarten pupils, ages 5-6 years from Aurora Quezon Elementary School, grouped into three with 10 subjects each. Each group received a corresponding behavior management technique: TSD, Desensitization-TSD, and Coping Skills Training-TSD. Then they underwent scaling and polishing and topical fluoride application. The Frank Rating scale was used to rate the behavior in three stages: before, during, and after treatment. Non-Parametric test results showed that Desensitization-TSD garnered the highest mean rank of 3.66 as compared to TSD, 3.01 and CST-TSD, 3.35. Significant difference was seen only in Desensitization-TSD in all stages of the treatment and in CST-TSD, only at the end of the treatment (p > 0.05). It was concluded that Desensitization-TSD seems to be a more effective behavior management technique for 5-6 years old pedodontic patients on their initial dental visit.